1978
DOI: 10.1007/bf00442160
|View full text |Cite
|
Sign up to set email alerts
|

Association of neonatal respiratory distress with birth asphyxia and deficiency of red cell mass in premature infants

Abstract: Red cell mass (RCM) was estimated using 125I-labelled human serum albumin in 128 premature infants born after 26 to 36 weeks gestation. Infants of three different gestational periods (26--29, 30--32, and 33--36 weeks) with respiratory distress (RD) averaged lower one-minute Apgar scores and lower RCM than infants without RD (P less than 0.05). The incidence of RD was significantly (P less than 0.05) higher in infants with Apgar scores below 6 and in infants with RCM of less than 35 ml/kg than in the infants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…This difference was not due to differences in birth weight or gestational age. It might have been due only to biologic variation or to a higher degree of birth asphyxia in the severe HMD group [12]. Unfortunately, Apgar scores from 5 study patients were not avail able, so this hypothesis could not be tested.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was not due to differences in birth weight or gestational age. It might have been due only to biologic variation or to a higher degree of birth asphyxia in the severe HMD group [12]. Unfortunately, Apgar scores from 5 study patients were not avail able, so this hypothesis could not be tested.…”
Section: Discussionmentioning
confidence: 99%
“…10 of the infants had received exchange transfusion immediate ly after birth. It is possible that some of these have been hypovolemic [29], but also the dy namic control of blood pressure may have been insufficient. Exchange transfusion increases colloid osmotic pressure in infants [30] and may have effects on the intravascular volume and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The number of infants receiving exchange transfusion was similar in all groups, and we think that it does not explain the intergroup differences. Infants with intra partum asphyxia do not participate in placen tal transfusion [29], which greatly modifies the neonatal blood volume [31]. Hypovolemia must be kept in mind as a cause of low ar terial blood pressure in these infants, especi ally in connection with poor peripheral circu lation and postnatal fall in hemoglobin [29].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Other studies indicated that ECC prevented placental transfusion and resulted in more respiratory distress syndrome among preterm infants. [11][12][13] Importantly, in settings with a high prevalence of HIV infection, immediate CC has been thought to reduce the risk of mother-to-child transmission. Furthermore, active management of third-stage labor, including use of oxytocin, together with ECC within 30 to 60 seconds and controlled cord traction, is considered important in the prevention of postpartum bleeding.…”
mentioning
confidence: 99%